Peran Supervisi Kepala Sekolah Dalam Meningkatkan Kinerja Di SDIT Muhammadiyah Al Kausar Tahun 2017 - Vulandari, Rosyita; , Drs. H. Rubino Rubiyanto, M.Pd (2017)
The aims of this research is to find out (1) bagaimana tujuan pelaksanaan supervisi kepala sekolah (2) supervision techniques (3) implementation of principal supervision (4) obstacles implementation of principal supervision (5) teacher performance. This research uses descriptive qualitative approach. Sources of data in this study include principals, curriculum waka, and teachers. Techniques used in collecting data are interview techniques, observation, and documentation. This research uses source triangulation and method triangulation, as well as using interactive analysis technique. The conclusions of this study include (1) the purpose of supervision of the principal, among others, so that teachers are more motivated in working, teachers always apply the rules, the quality of learning activities to be better, administration equipment, and to advance the school. (2) the implementation of supervision includes planning, implementation and evaluation activities. (3) obstacles in the implementation of supervision include the number of principal's agenda, the number of teachers and employees so that sometimes the implementation is uneven (4) in implementing teacher learning preparing RPP every 1 semester, teachers use instructional media adapted to the teaching materials and conditions of students, teachers Using methods and strategies in each learning tailored to the teaching materials and characteristics of students. (5) the implementation of supervision carried out by the principal and assisted by waka curriculum has been classified smoothly and the performance of teachers increased after the supervision.